Magnetotransport properties near the Dirac point of Dirac semimetal Cd3As2 nanowires. (29th November 2016) - Wang, Li-Xian; Wang, Shuo; Li, Jin-Guang; Li, Cai-Zhen; Xu, Jun; Yu, Dapeng; Liao, Zhi-Min
Abstract: Three-dimensional (3D) Dirac semimetals are featured by 3D linear energy-momentum dispersion relation, which have been proposed to be a desirable system to study Dirac fermions in 3D space and Weyl fermions in solid-state materials. Significantly, to reveal exotic transport properties of Dirac semimetals, the Fermi level should be close to the Dirac point, around which the linear dispersion is retained. Here we report the magnetotransport properties near the Dirac point in Cd3 As2 nanowires, manifesting the evolution of band structure under magnetic field. Ambipolar field effect is observed with the Dirac point at V g   =  3.9 V. Under high magnetic field, there is a resistivity dip in transfer curve at the Dirac point, which is caused by the Zeeman splitting enhanced density of state around the Dirac point. Furthermore, the low carrier density in the nanowires makes it feasible to enter into the quantum limit regime, resulting in the quantum linear magnetoresistance being observed even at room temperature. Besides, the dramatic reduction of bulk conductivity due to the low carrier density, together with a large surface to volume ratio of the nanowire, collectively help to reveal the Shubnikov–de Haas oscillations from the surface states. Our studies on transport properties around the Dirac point therefore provide deep insights into the emerging exotic physics of Dirac and Weyl fermions.